Attempts to improve on the V‐hull structural design for air‐blast loading applications. Issue 2 (1st September 2021) - Langdon, Genevieve; Curry, Andrew; Shekhar, Vinay; Siddiqui, Aashir; Murray, Christopher; von Klemperer, Chris
Abstract: Mine resistant ambush protected vehicles often use mono‐V structures in the design of their hulls for blast protection purposes. These hulls deflect blast waves laterally in the event of a landmine detonation directly beneath the vehicle. Lower internal angles offer greater deflection capability, reducing the impulse transfer to the vehicles, but at the cost of increased ride height. This paper reports results of attempts to improve on V‐hull structural designs for air‐blast loading applications, where scaled blast tests are performed to evaluate the designs in terms of structural deformation, rupture and impulse transfer characteristics. Structures with double V and W profiles are compared to mono V structures with a 120° internal angle, such that the proposed designs do not increase the ride height. Results showed that the double V‐structures limit the central deformation, but some designs have severe deformation at the interface of the central V plate and the shallow base angle structure. W structures seem to be susceptible to rupture at low charge masses. There is no single answer to improved blast protection of vehicle hulls, as design choices must be driven by the anticipated threat range, the important performance metrics and other operational considerations.